Forensic engineering testing techniques for structural assesment : a case study on pre-stressed reinforced concrete bridge at Klang Valley - Muniandy, Gopinath (2010)
Integrity test on existing concrete structures is often being carried out to determine the assessment for the structure through several aspects such as to determine the whether the structure is suitable for its designed use, for proposed change of usage or extension of a structure, to enswe the acceptability of structure following to any deterioration or structural damage. The evaluation of integrity of existing concrete structures has been carried out through several testing methods and procedures such as non destructive test (NDT) and partially destructive test using sophisticated testing techniques. However, the criteria of selection for suitable testing method and techniques is still are being unclear depending types of structure that need to be tested. The criteria determination of most suitable codes and standards specification for Malaysia perspective is also unclear. Therefore, it is vital to study the reality in selecting most suitable testing method incorporated with most suitable codes and standardizations to carry out integrity test on existing concrete structures in Malaysia. This case study consisting testing on existing concrete structures using concrete core method, rebound hammer test and ultra sonic pulse velocity OJPV) on existing prestressed T-beam and concrete structures of an unnamed bridge in Klang Valley. Results obtained from testing tabulated for comparison between BS 1881& BS 6089 cube characteristic strength and BSEN 13791, 2007 cube characteristic strength. Selected civil and structural consulting engineers was interviewed using prepared questionnaire to identify the selection criteria and views in selecting appropriate testing method to evaluate integrity of existing concrete structures. Finally, the factors influencing selecting the most suitable testing method and comparison of selected standard code and practice identified.